Antimicrobial peptides in gastrointestinal diseases - Cho, C.-H. (Chi-Hin) (Academic Press, an imprint of Elsevier, 2018)
Antimicrobial peptides (AMPs), including cathelicidins and defensins are host defence peptides that carry out multiple roles in the gastrointestinal (GI) tract. Antimicrobial Peptides in Gastrointestinal Diseases presents knowledge about the physiological functions and pharmacological actions of AMPs in inflammation, cancer, and further infection of the GI tract. The book provides coverage from the basic research to clinical application for GI diseases. Current research and development of AMPs is presented, opening the way for further work on these peptides, not only in the context of GI diseases, but also for similar pathologies in other organs. AMPs are key to the regulation of human microbiome and second line defence in the GI mucosa, prevent colonization of pathogens and modulation of innate response to invading pathogens, and modify immunological reactions during inflammatory processes and oncogenic development in the GI mucosa. More importantly, AMPs possess diversified anti-microbial actions against various infectious diseases in the GI tract. With these physiological functions and pharmacological actions, AMPs have significant potential as therapeutic agents for the treatment of inflammation, cancer and further infection in the GI tract. Provides an overview of AMPs, particularly cathelicidin and defensin, in different diseasesCovers inflammation and ulcer repair in the stomach and colon and carcinogenesis in the GI tractPresents AMP information and knowledge in a concise mannerGives useful information on all aspects of AMPsPromotes research on AMPs and their development as drugs, from bench, to clinical application.